Understanding the Structure‐Activity Relationship of Ni‐Catalyzed Amide C−N Bond Activation using Distortion/Interaction Analysis - Xie, Pei‐Pei; Qin, Zhi‐Xin; Zhang, Shuo‐Qing; Hong, Xin (ChemCatChem, 2021)
Transition metal‐catalyzed amide C−N bond activation has emerged as a powerful strategy to utilize amides in synthetic transformations. The key mechanistic basis for the rational design of amide reagents is the structure‐activity relationship of amide C−N bond activation. In this work, the controlling factors of Ni/PCy3‐catalyzed amide C−N bond activation barrier are elucidated with density functional theory (DFT) calculations and distortion/interaction analysis. We found that the substrate distortion is the key factor that differentiates the amide reactivity in the C−N bond activation. The substrate distortion of amide is associated with two distinctive structure‐activity relationships. The general planar amides undergo a classic three‐membered ring oxidative addition to cleave the C−N bond, in which the C−N heterolytic bond dissociation energy has a linear relationship with the activation barrier. The twisted amides have a chelation‐assisted transition state for the amide C−N bond cleavage, and the twisted angle τ can serve as a predictive parameter for the reactivity of the twisted amides. The understanding of the structure‐activity relationship of amide C−N bond activation provides a rational and predictive basis for future reaction designs involving transition metal‐catalyzed amide C−N bond activation. Computational catalysis: The structure‐activity relationship and the key controlling factors of amide activation barriers were elucidated by DFT calculation and distortion/interaction analysis.